Design and Implementation of Earthquake Emergency Response System Based on Grid Data. (June 2018) - Zhao, J; Ma, Z H
Abstract: Generally speaking, the estimate of casualty, economic loss and damage of building or structures after earthquakes is modelled through the evaluating seismic influence field and the data which is administrative units for census and statistics. Thus, the evaluating results have good application in large scale, but are not accurate enough in the case of post-earthquake disaster assessments. The data based on kilometre grid can better embody the spatial heterogeneity of elements. And then it would improve the accuracy of the assessments. The paper introduces the design and implementation of earthquake emergency response system based on the kilometre grid data in Shanxi province of population, economy, and housing from several facets, such as system architecture, technology implementation, database design, functional modules and algorithms, system workflows and product details. Taking the 2010 M4.8 Hejin earthquake as an example, the evaluation is fast, precise, and spatial heterogeneity of the disaster pre-assessment is obvious.